PENGARUH PAD, DAU, DAN DAK TERHADAP BELANJA MODAL PEMERINTAH DAERAH - Safiul Huda; Ati Sumiati (Jurnal Ilmiah Wahana Akuntansi, 2019)
This research aims to examine the effect of Regional Original Income, General Allocation Funds, and Specific Allocation Funds for Capital Expenditures both partially and simultaneously. The subjects in this study were Regency/ City Regional Governments in Central Java Province. This research used a sample of 32 regencies/ cities in Central Java originating from the Regional Revenue and Expenditure Budget (APBD) Report from 2014-2016 obtained from the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia. The data analysis technique used is multiple linear regression with hypothesis testing using t-statistics and F-statistics and coefficient of determination. The results of the research provide information that Regional Original Income and General Allocation Funds have an effect on Capital Expenditures, while Special Allocation Funds do not affect Capital Expenditures.